Analysis of infections, recoveries and deaths from COVID-19 in rivers state, Nigeria - ADEDIRE, Oludare; JONH, Walter C.; OLA OOLADEJO, Afolabi; ONUWA, Godfrey; JEPTHAH MBAH, Jacob (One Health & Risk Management, 2023)
Introduction: While some patients recovered, others died across the world thereby losing their loved ones. The objective of the current study is to determine statistical difference in means of COVID-19 infected population (laboratory confirmed), discharged cases(recovered) and deaths resulting from COVID-19 pandemic in Rivers State, Nigeria.Material and Methods: In this study, extraction of infected population (laboratory confirmed), discharged cases and deaths from COVID-19 was carried out from data obtained from Nigeria Centre for Disease Control which covered a period of 572 days (25th March 2020 - 17th  October  2021). The test for significance of means among the variables was done using one-way Analysis of Variance (ANOVA) followed by Tukey HSD test. The two variables whose means do not significantly differ were tested for strength of relationship and dependence using correlation analysis and cubic polynomial function respectively.Results: Results showed  that there is statistically significant difference between infected population, discharged cases and deaths from COVID-19 as obtained from one-way ANOVA (F(2, 1710) = 121.958, p = 0.000). Use of Tukey HSD test indicated that means of infected population and discharged cases do not differ from each other (p>0.01); however, mean deaths from COVID-19 significantly differ from others at 99%  confidence intervals (p<0.01). There was weak positive relationship between deaths due to COVID-19 and  other  two groups (r=0.360, n=571, p=0.000).  However, moderate positive correlation existed between COVID-19 infected population and discharged population (r=0. 566, n=571, p=0.000) at  99% confidence interval.Conclusions: Mean of deaths from the study population was significantly different from means from both infected population and discharged (recovered) cases. This implies that only few people died from COVID-19  in Rivers State Nigeria when compared to  those who got infected and recovered from COVID-19 pandemic.